Inskripsi Keagamaan Nusantara di Palu Sulawesi Tengah - Dede Burhanudin (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2016)
Religious inscriptions often cannot be separated from religious doctrines developed by the local communities in relation to their level of understanding of religion. In Central Sulawesi, religious teachings acquired from the teachers, scholars and religious leaders of Islam have colored the form and content of religious inscriptions. This article discusses the history and development of some religious inscriptions in Central Sulawesi, primarily in the cities of Palu, Donggala, and Banggai. The study focuses on four areas, namely (1) The family cemetery of Tanga Banggo (Kings of Palu), (2) the Mosque of Kampung Baru in Kota Palu, (3) the Al-Amin Mosque in Wani, Donggala, and (4) The Grand Mosque of Donggala in Donggala. From these areas, the research found 46 inscriptions. The inscription on the tombstone consists of identity and titles of the deceased, prayers, verses of the Qur’an, and the name of the Prophet's family and Companions. Meanwhile, the inscription on the mosques consists of the mosque names, the year of construction, and Hadith. Calligraphy is used generally in the styles of Tsulutsi, and Naskhi. The materials used consisted of wood, river rock, stone and marble temples. The existing conditions of inscriptions on tombstones, generally have suffered damage (wear). Headstone size generally between 20-120 centimeters. Headstone for men mostly spherical (phallus) and for women are usually flat. At the cemetery, the inscription contains the pilgrimage to the cemetery or graves, especially the graves Islamic leaders generally have similarities with other regions in Indonesia. While encryption in mosques suggests the words of prayers five times a day, away from God’s prohibition, hoping to worship for Allah's pleasure, advice, obedience, and others. Keywords: Religious Inscription, Mosques, Tombs, Islam, History, Central Sulawesi Inskripsi kegamaan seringkali tidak dapat dipisahkan dari kepercayaan masyarakat setempat dalam hubungannya dengan tingkat pemahaman mereka terhadap agamanya. Di Sulawesi Tengah, ajaran agama yang diperoleh dari para guru, ulama dan pimpinan agama Islam sedari awal mewarnai bentuk dan isi inskripsi keagamaan. Artikel ini membahas sejarah dan perkembangan beberapa inskripsi keagamaan di provinsi Sulawesi Tengah, tepatnya di kota yaitu Palu, Donggala, dan Banggai. Penelitian di fokuskan pada empat lingkungan, yaitu (1) Makam Situs Pekuburan Keluarga Tanga Banggo (Raja-Raja Palu), (2) Masjid Jami Kampung Baru Kota Palu, (3) Masjid Al Amin Wani di Donggala, dan (4) Masjid Raya Donggala di Donggala. Penelitian ini menemukan 46 inskripsi. Inskripsi pada nisan terdiri dari identitas dan gelar orang yang meninggal, doa, ayat al-Qur’an, dan nama keluarga dan sahabat Nabi. Sementara itu, inskripsi di Masjid terdiri dari nama masjid, tahun pembangunannya, dan hadis. Kaligrafi yang digunakan umumnya memakai Arab tsulutsi, dan naskhi. Adapun bahan yang digunakan terdiri dari kayu, batu sungai, batu candi dan marmer. Keadaan inskripsi yang ada pada nisan, umumnya telah mengalami kerusakan (aus). Ukuran nisan pada umumnya antara 20 - 120 cm. Nisan untuk laki-laki kebanyakan berbentuk bulat (lingga) dan untuk perempuan pipih. Di pekuburan, inskripsi berisikan ziarah ke pemakaman atau kuburan, terutama kuburan pemuka-pemuka Islam yang banyak kesamaan dengan daerah lainnya di Indonesia. Sementara inkripsi yang ada di masjid banyak menjelaskan masalah salat lima waktu, menjauhi larangannya, ibadah untuk mengharap rida Allah, nasehat, ketaatan, dan lain-lain. Kata kunci: Prasasti Keagamaan, Masjid, Kuburan, Islam, Sejarah, Sulawesi Tengah